The role of Indonesian herbal medicine in disease prevention, treatment, and rehabilitation among international communities in Kuantan, Malaysia - Lolita, Lolita; Ikhsanudin, Azis; Osman, Ahmed Mohamed Yehia; Osman, Muhamad Faris; Bhatti, Zohra; Intan Sari, Septia Verda; Nurani, Laela Hayu; Sulistyani, Nanik; Azzahra, Fara; Wicaksono, Anggoro; Hendryawan, Andhika Noor (UAD Press, 2025)
Background: Indonesian herbal medicine has been utilized for communities in the prevention, treatment, and rehabilitation of various health conditions, as well as in the promotion of overall well-being. It is also commonly used as a complementary approach alongside modern medical therapies.